Post a New Question

algebra

posted by .

Simplify the expressions.
1. (-6c^2)(2c^2-3c)
2. (-5d-10d^2)(-6d^3)
3. x^3-(4x+3x^2)(x^2)
4. (-8y^2)(3y-4)+6y^2-5y^3
5. (18m/-4n) / (-1/4m)
6. (5x^2) / (2x/15)
7. (-16x+9) / (-4)
8. (-32-4x) / (-8)

I don't get how to do these. Please help!! Thanks a lot!! =)

  • algebra -

    First you have to study the laws of exponents, which include:
    ax * ay = ax+y
    ax / ay = ax-y
    ax * ay = (ax+y)y = axy
    a-x = 1/ax
    a1/x = xth root of a

    When you have a multiplication of powers, you would group together factors with the same base and apply the above rules.
    I will do the first one to give you a kick-start.
    (-6c^2)(2c^2-3c)
    = -6 (c²)(2c²-3c)
    = -6 (2c2+2 - 3c2+1)
    = -6(2c⁴-3c³)
    = -12c⁴+18c³)

  • algebra -

    You can now attempt the rest of the problems and send in your answers for checking if you wish.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question